Tenascin: cDNA cloning and induction by TGF-beta. - Pearson, C A (1988)
cDNA clones coding for tenascin, an extracellular matrix glycoprotein with a restricted tissue distribution, were isolated from a chicken fibroblast cDNA expression library using a specific tenascin antiserum. Antibodies eluted from the cDNA-encoded fusion proteins reacted exclusively with tenascin. Limited trypsin treatment of purified tenascin resulted in a peptide which confirmed the deduced protein sequences. The largest clone encoding 632 amino acids showed a cysteine-rich region containing 13 consecutive epidermal growth factor-like repeats of unusual uniformity. Northern blot analysis revealed 8- to 9-kb messages. Tenascin is shown to be induced in vitro by fetal calf serum as well as by transforming growth factor beta (TGF-beta). A 4-fold increase in tenascin secretion by chick embryo fibroblasts was seen after TGF-beta treatment. The induction of tenascin protein synthesis was preceded by an increase of tenascin mRNA as determined by Northern blot analysis. The induction of tenascin was compared with fibronectin. The accumulation of the two extracellular matrix proteins in the medium was differentially affected by fetal calf serum and TGF-beta and the increase was in both cases higher for tenascin.